Role of Specific Quorum-Sensing Signals in the Regulation of Exopolysaccharide II Production within Sinorhizobium meliloti Spreading Colonies - Gao, Mengsheng (Public Library of Science, 2012)
BACKGROUND: Quorum sensing (QS) in Sinorhizobium meliloti involves at least half a dozen different N-acyl homoserine lactone (AHL) signals. These signals are produced by SinI, the sole AHL synthase in S. meliloti Rm8530. The sinI gene is regulated by two LuxR-type transcriptional regulators, SinR and ExpR. Mutations in sinI, sinR and expR abolish the production of exopolysaccharide II (EPS II). METHODOLOGY/PRINCIPAL FINDINGS: This study investigated a new type of coordinated surface spreading of Rm8530 that can be categorized as swarming. Motility assays on semi-solid surfaces revealed that both flagella and EPS II are required for this type of motility. The production of EPS II depends on AHLs produced by SinI. Of these AHLs, only C(16:1)- and 3-oxo-C(16:1)-homoserine lactones (HSLs) stimulated swarming in an ExpR-dependent manner. These two AHLs induced the strongest response in the wggR reporter fusions. WggR is a positive regulator of the EPS II biosynthesis gene expression. The levels of the wggR activation correlated with the extent of swarming. Furthermore, swarming of S. meliloti required the presence of the high molecular weight (HMW) fraction of EPS II. Within swarming colonies, a recombinase-based RIVET reporter in the wggR gene was resolved in 30% of the cells, indicating an enhanced regulation of EPS II production in the subpopulation of cells, which was sufficient to support swarming of the entire colony. CONCLUSIONS/SIGNIFICANCE: Swarming behavior of S. meliloti Rm8530 on semi-solid surfaces is found to be dependent on the functional QS regulatory cascades. Even though multiple AHL signals are produced by the bacterium, only two AHLs species, C(16:1)- and 3-oxo-C(16:1)-HSLs, affected swarming by up-regulating the expression of wggR. While EPS II is produced by Rm8530 as high and low molecular weight fractions, only the HMW EPS II facilitated initial stages of swarming, thus, suggesting a function for this polymer.